Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa dengan Model Pembelajaran Kooperatif Tipe STAD di SMAN 2 Mataram - Aan Putra Setiawan; Sutarto Sutarto; Sri Yuliyanti (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2025)
Abstract: The aim of this research is to improve mathematical problem solving abilities using the STAD type cooperative learning model in Class XI Saintek 4 SMAN 2 Mataram Academic Year 2023/2024. This research is classroom action research (PTK). The classroom action research procedure for each cycle consists of four stages, namely the planning, implementation, observation and reflection stages. The instruments used were teacher and student observation sheets, and student test sheets. Based on the research result, it shows that the results of students’ abilities increased from the initially low results obtained, namely 34,375 % to 91,428 %. the results of teacher observation and student’s observation which were initially low at the begininning of the cycle experienced a significant increase at the end of the cycle. Thus, it can be concluded that the STAD Type Cooperative learning model can improve students' problem solving abilities so it is hoped that teachers will ensure that in the teacher's teaching and learning process can apply the STAD Type Cooperative learning model.